IPO Under-pricing of pharmaceutical companies in China between 2010 and 2015 - Yu, Meng Hui (2016)
The extremely high A-share Initial public offerings (IPOs) under-pricing in China’s primary market provides us with a very interesting area of empirical research. This study focuses on the pharmaceutical industry which is a knowledge-based, technology-intensive industry and has become one of the leading industries in China. Based on regression analysis of 66 pharmaceutical A-shares companies that went public through IPOs at both Shanghai and Shenzhen Stock Exchanges in China during 2010-2015, we find that 89.4% of pharmaceutical firms were undervalued. This study also finds that 1) IPO underpricing is negatively related to the firm size (asset) and positively related to IPO volume; 2) issuing time and underwriter reputation have no impact on IPO underpricing. The paper further discuss and analyse the potential and analyse the potential and specific factors that may have influence on IPO underpricing due to the pharmacy industry’s particularity, besides these factors have been lacking in the IPO literature.